HUBUNGAN PENGETAHUAN DAN SIKAP TERHADAP TINDAKAN HIGIENE SANITASI PENGOLAHAN MAKANAN JAJANAN PEDAGANG KAKI LIMA DI PERUMNAS SIMALINGKAR KECAMATAN MEDAN TUNTUNGAN KOTA MEDAN TAHUN 2023 - Deli Syaputri (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2024)
Street vendors' knowledge regarding food processing sanitation hygiene will determine their attitudes, and this will influence the vendors' actions when processing food. Sanitary hygiene in street food processing is a health effort by maintaining and protecting cleanliness. Personal hygiene in food processing can be achieved if an understanding of the importance of maintaining personal health and cleanliness is embedded within oneself. The aim of this research is to determine the relationship between knowledge and attitudes towards sanitary hygiene measures for processing street food snacks at Perumnas Simalingkar in 2023. This research is analytical with a cross sectional design, which means a study where the variables including effects are observed. The sample used in this research used total sampling. The total sample size is all 35 street food traders. The data was analyzed using the chi square test. Based on the results of the chi square test, there is a relationship between knowledge of food sanitation hygiene measures with a p value of 0.019, and there is a relationship between attitudes towards food sanitation hygiene measures with a p value of 0.019. The research conclusion is that there is a relationship between knowledge and action and there is a relationship between attitude and action. The advice that researchers can give is to take part in training and counseling on food sanitation hygiene in order to guarantee the quality of the food to be sold.